Global trends in ICT-based extension and advisory services in agriculture: a bibliometric analysis - Mukherjee, Sweety; Padaria, Rabindra Nath; Burman, Rajarshi Roy; Velayudhan, Praveen Koovalamkadu; Mahra, Girijesh Singh; Aditya, Kaustav; Sahu, Subhashree; Saini, Sushmita; Mallick, Sonali; Quader, Sk. Wasaful; Shravani, K.; Ghosh, Bhaskar; et al. (Frontiers in Sustainable Food Systems, 2025)
Utilizing Information and Communication Technology (ICT) to grant farmers direct access to information, while also developing models tailored to the specific contexts of both public and private agricultural extension sectors, stands as a pivotal endeavor in modern agriculture. This study uses bibliometric analysis to identify key research areas in ICT-based extension and advisory services (EAS) and to understand patterns and trends within this domain. The Scopus database served as the primary tool for accessing publications, yielding a corpus of 525 articles spanning from 1999 onwards, subsequently analyzed through VOSviewer and R software. The findings unveil that the Sustainability journal claims the highest number of published articles, while the Agricultural Economics journal garners the most citations within this realm. Notably, Aker emerges as the most globally cited author with 405 citations, while China Agricultural University emerges as the institution with the highest publication count concerning ICT-based EAS. India emerges as a frontrunner with 446 publications, while publications originating from the USA receive the highest number of citations, reflecting the nation's substantial endeavors and investments in harnessing ICT for agricultural extension purposes. The co-occurrence analysis of all keywords emphasizes the primary focus of publications on e-agriculture and e-extension. Furthermore, the outcomes of co-citation analysis highlight The Journal of Agricultural Education and Extension as the most referenced journal, with 22 citations and a cumulative link strength of 266, indicative of its profound influence and recurrent citation alongside other scholarly journals. This study uncovers an escalating interest in this field, emphasizing its paramount importance in contemporary agricultural practices. Accordingly, these findings offer crucial insights for guiding future research and shaping evidence-based policies, thereby aiding researchers, policymakers, and practitioners in improving ICT-based EAS in agriculture.